Failure to Thrive in an Older Adult: A Case-Based Exercise for Medical Students - Amy C. Denham; Gary Winzelberg (Association of American Medical Colleges, 2013)
Abstract This case-based exercise designed for second-year medical students covers principles of diagnosis and management of failure to thrive in older adults. It provides a structured team-based setting in which groups of medical students can practice clinical reasoning skills. It has been used as part of a series of clinical cases created to help students synthesize what they have learned in different organ system courses and apply their knowledge to geriatric practice. The exercise could be used at various points in medical students' training, but participants should have completed some basic coursework in principles of geriatric medicine, as well as hematology, cardiology medicine, and gastroenterology. This case requires preclinical students to integrate and synthesize learning from many different courses and disciplines. In our experience, the modified team-based learning approach that this exercise employs generates lively and clinically sophisticated discussions among second-year medical students.